Sikap Pemustaka Terhadap Layanan Sirkulasi di Perpustakaan Universitas Negeri Padang - Dewi, Sri Terta; Ardoni, Ardoni (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this paper to determine the attitude towards the service user at the library circulation Padang State University. Data were collected through questionnaires and interviews with users at the Library of the Padang State University. The study's finding share, first, the attitude towards the service user's circulation, which tends to be positive because the service is good and easy to do. Second, the attitude of users towards circulation librarian, which tend to be negative because the librarian was not friendly and the information is sometimes not clear. Third, the user attitude towards the collection in circulation services at the library, which is likely to be negativebecause of the number of collections that are not varied and irregular arrangement are difficult for users to find the required book. Fourth, the user attitude towards service rules circulation, which tends to be positive because these rules are not arbitrary student with leeway given library. Fifth, the user attitude towards the service time of circulation, which is likely to be negative because the clock does not match the needs of service users. Sixth, the user attitude towards a given facility library circulation services, which tend to be positive because the rooms were quite comfort and fast search tool and easy to use. Keywords: attitude; library; service; circulation